PENGEMBANGAN INSTRUMEN PENGUKUR HASIL BELAJAR NIRBIAS DAN TERSKALA BAKU - Mardapi, Djemari; Kartowagiran, Badrun (Jurnal Penelitian dan Evaluasi Pendidikan, 2013)
Penelitian hibah ini bertujuan untuk mengembangkan instrumen pengukur hasil belajar yang nirbias dan terskala baku yang digunakan dalam beberapa mata pelajaran di SMA dan atau SMP. Jenis penelitian ini adalah research and development (R&D) yang dilakukan selama dua tahun. Hasil penelitian tahun pertama dihasilkan draf instrumen pengukur hasil belajar yang nirbias dan terskala baku. Tahun kedua, diseminasi draf instru-men pengukur hasil belajar yang dihasilkan tahun pertama ke beberapa guru Matematika SMA dan SMP di Provinsi DIY dan Jawa Tengah. Setelah direvisi, instrumen disosialisasikan ke be-berapa guru Matematika SMA dan SMP di Provinsi DIY, Jawa Tengah dan NTB. Kata kunci: instrumen yang nirbias dan terskala baku ______________________________________________________________ DEVELOPING UNBIASED AND STANDARDIZED INSTRUMENTS FOR STUDENT ACHIEVEMENTS IN HIGHSCHOOLS Abstract The purpose of this research is to develop unbiased and standardized instruments to measure student achievements that can be used for several subject matters in senior high schools and junior high schools. This was a research development study carried out in two years. The result of this research in the first year was a draft of an unbiased and standardized instuments for student achievements. In the second year, the draft of the unbiased and standardized instruments was disseminated to several mathematics teachers in senior high schools and junior high schools in the provinces of Yogyakarta Special Territory and Central Java. After the revision, the instruments were disseminated again to mathematics teachers in senior high schools and junior high schools in the provinces of Yogyakarta Special Territory, Central Java, and Nusa Tenggara Barat. Keywords: unbiased instruments, standardized instruments